2020
DOI: 10.1109/access.2020.2997879
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and Rhythm Transition in a Complex Neuronal Network

Abstract: Synchronization and rhythm transition in an excitatory-inhibitory balanced cortical neuronal network are investigated in this paper. A small-world neuronal network is performed to be the cortical region of cerebral cortex, which is composed of different types of Izhikevich neurons. The combination of regular spiking (RS) cells, chattering (CH) cells, or mixed RS and CH cells are imitated as excitatory neurons, whereas fast spiking (FS) cells mimic inhibitory neurons. We mainly focus on the effect of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The neuron cluster is in the inhomogeneously asynchronous state, and the redundancy between neurons is lower, and the network interaction ability is weaker than the network computing ability. When w e = 0.35, all of the neurons are in the complete synchronous firing state ( Figure 10C ) (Wang et al, 2020 ). When the coupling strength reaches a specific strength ( w e = 1), the MIZH spiking network exhibits another spatiotemporal pattern (the top plot in Figure 10D ).…”
Section: The Pulse-coupled Mizh Spiking Model With Cortical-like Coll...mentioning
confidence: 96%
See 1 more Smart Citation
“…The neuron cluster is in the inhomogeneously asynchronous state, and the redundancy between neurons is lower, and the network interaction ability is weaker than the network computing ability. When w e = 0.35, all of the neurons are in the complete synchronous firing state ( Figure 10C ) (Wang et al, 2020 ). When the coupling strength reaches a specific strength ( w e = 1), the MIZH spiking network exhibits another spatiotemporal pattern (the top plot in Figure 10D ).…”
Section: The Pulse-coupled Mizh Spiking Model With Cortical-like Coll...mentioning
confidence: 96%
“…The synchronous neural phenomenon is involved in a series of higher-level brain functions and neuronal processes (Liu and Shi, 2018 ). Synchronous activities play a crucial role in information processing and signal encoding of the cerebral cortex (Wang et al, 2020 ). The asynchronous behavior is the pivotal part of the intermediary between information propagation and transformation.…”
Section: The Pulse-coupled Mizh Spiking Model With Cortical-like Coll...mentioning
confidence: 99%
“…Content may change prior to final publication. networks [4][5][6][7][8][9][10][11][12][13][14][15]. The relevant literature shows that the main factors affecting the synchronization of coupled neuronal networks are the network topology [4][5][6][7][8], time delay in the network [9,10], coupling strength [11][12][13][14], and multilayer network structure [15], etc.…”
Section: Introductionmentioning
confidence: 99%
“…networks [4][5][6][7][8][9][10][11][12][13][14][15]. The relevant literature shows that the main factors affecting the synchronization of coupled neuronal networks are the network topology [4][5][6][7][8], time delay in the network [9,10], coupling strength [11][12][13][14], and multilayer network structure [15], etc. Recently, researchers have found that the electrical activity of neurons may be affected by electromagnetic fields, and thus, electromagnetic fields can be detected by the neuronal system [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…R ECENTLY, the complex networks (CNs) have gained growing attentions because of their widely applications such as smart grids, social networks, communication networks and so on [1]- [5]. One of the emphases for CNs research is the synchronization problem, which refers to a coherent phenomenon between two or more systems.…”
Section: Introductionmentioning
confidence: 99%